The Impact of the Campus Teaching Program Batch 4 of Dongko 1 Public Middle School in Improving Students' Literacy and Numeracy Skills - Anita Agustiani (Formosa Journal of Social Sciences (FJSS), 2022)
The Covid 19 pandemic entered Indonesia from 2020, this resulted in children's study time at their respective homes and carried out online. This study aims to describe the impact of implementing the campus teaching program in improving the literacy and numeracy of students at SMPN 1 Dongko. The research method used is a qualitative method. The subjects of this study were students in class VIII D, which consisted of 30 students. Data collection was carried out using observation and documentation techniques. The benefits of the Campus Teaching program empower students to assist in administrative activities, technology adaptation and teaching and learning activities in schools. Especially schools that are in the 3T area (frontier, outermost, and lagging). The activities that the authors carry out in the Teaching Campus program are assisting with teaching, assisting with technology adaptation, and assisting with school administration. The teaching campus program implemented at Dongko 1 Public Middle School is very beneficial for the school and students. In addition, with the Teaching Campus program, students can add insight, friendships and experiences outside of college